Unfavorable Course of Subclinical Hypothyroidism in Children with Hashimoto’s Thyroiditis Compared to Those with Isolated Non-Autoimmune Hyperthyrotropinemia - Lee, Yun Jeong; Jung, So Yoon; Jung, Hae Woon; Kim, So Youn; Lee, Young Ah; Lee, Seong Yong; Shin, Choong Ho; Yang, Sei Won (Journal of Korean medical science, 2017)
Subclinical hypothyroidism (SCH) is a common problem in pediatric population, and the natural history of SCH varies depending on its etiology. Whether Hashimoto's thyroiditis (HT) negatively affects the natural course of SCH was investigated in pediatric patients without concomitant diseases. Predictors for levothyroxine medication were also evaluated. Medical records of 109 children with SCH (91 girls, 5?18 years) diagnosed between 2005 and 2014 were retrospectively reviewed. Patients were classified into HT (n = 37) and isolated non-autoimmune hyperthyrotropinemia (iso-NAHT, n = 72). During median 2 years of follow-up, only 10.1% of SCH patients eventually initiated levothyroxine, and HT patients showed a higher probability of requiring levothyroxine medication than iso-NAHT patients (21.6% vs. 4.2%). Underlying HT independently predicted deterioration of thyroid function, leading to levothyroxine medication (hazard ratios [HRs], 4.6 vs. iso-NAHT, P = 0.025). High titers of anti-thyroglobulin antibodies (TGAbs) predicted later medication in the HT group (HRs, 28.2 vs. normal TGAbs, P = 0.013). Most pediatric SCH showed benign and self-remitting courses. Underlying HT significantly increases the risk for levothyroxine medication, especially with high titers of TGAbs.